2022
DOI: 10.3389/fmicb.2022.1056637
|View full text |Cite
|
Sign up to set email alerts
|

Short-term head-down bed rest microgravity simulation alters salivary microbiome in young healthy men

Abstract: Microgravity influences are prevalent during orbital flight and can adversely affect astronaut physiology. Notably, it may affect the physicochemical properties of saliva and the salivary microbial community. Therefore, this study simulates microgravity in space using a ground-based −6° head-down bed rest (HDBR) test to observe the effects of microgravity on oral salivary secretion function and the salivary microbiome. Sixteen healthy young male volunteers were recruited for the 15-day −6° HDBR test. Non-stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…The innermost tree structure refers to the OTU phylogenetic tree: each branch represents a species, and the length of the branch is the evolutionary distance between two species, i.e., the degree of species difference. examine saliva samples from volunteers under simulated microgravity conditions and found that the structure of the microbial community during HDBR differed from that before HDBR (Sun et al, 2022). However, Sun et al (2022) did not observe differences in the abundance of salivary microbial communities during HDBR compared to before HDBR.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…The innermost tree structure refers to the OTU phylogenetic tree: each branch represents a species, and the length of the branch is the evolutionary distance between two species, i.e., the degree of species difference. examine saliva samples from volunteers under simulated microgravity conditions and found that the structure of the microbial community during HDBR differed from that before HDBR (Sun et al, 2022). However, Sun et al (2022) did not observe differences in the abundance of salivary microbial communities during HDBR compared to before HDBR.…”
Section: Discussionmentioning
confidence: 87%
“…Beta diversity analysis revealed significant differences in the structure of the supragingival plaque microbial community before and during HDBR and in the recovery state. Our group previously used 16S rRNA gene sequencing to examine saliva samples from volunteers under simulated microgravity conditions and found that the structure of the microbial community during HDBR differed from that before HDBR ( Sun et al, 2022 ). However, Sun et al (2022) did not observe differences in the abundance of salivary microbial communities during HDBR compared to before HDBR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies suggested salivary changes in the microgravity environment. Sun examined the effects of microgravity on oral salivary secretory function and the microbiome in a simulated microgravity environment for 15 days and observed no significant pH, flow rate, or alpha diversity differences but noticed an increase in oral disease-related bacteria and decreased oral health-related commensal bacteria [ 15 ]. However, Rai et al concluded that flow rate, sodium, potassium, calcium, phosphate, and protein levels were increased in microgravity simulation environments compared to normal, and the same findings were observed in urine.…”
Section: Reviewmentioning
confidence: 99%